Animal rights - Bloyd, Sunni (San Diego, CA : Lucent Books, 1990)
Discusses current animal rights issues, their underlying philosophies, and ways we can held curb animal abuse.
Includes bibliographical references (p. 123-124) and index.
Elem. School Library Collection.
School Library Journal.
7.6
7.6
5-8.
Keywords: Animal rights -- Juvenile literature; Animal welfare -- Juvenile literature; Animal rights; Animals -- Treatment; Animal welfare